2016
DOI: 10.1097/icl.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Eye Cosmetics on the Eye, Adnexa, and Ocular Surface

Abstract: Despite the fact that cosmetic products undergo rigorous testing to ensure they are safe for human use, some users report mild discomfort following their application. The cutaneous changes, such as allergic dermatitis, are well reported, but the ocular changes associated with eye cosmetic use are less so. Some pigmented cosmetic products may accumulate within the lacrimal system and conjunctivae over many years of use, but immediate reports of eye discomfort after application are most common. Changes to the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 98 publications
0
32
0
15
Order By: Relevance
“…The migration of externally applied eye cosmetics onto the ocular surface has been consistently reported 6,7,11,12,14. There have been numerous anecdotal accounts of tear film contamination with eye cosmetic products during routine slit lamp examination 6,12.…”
Section: Ocular Migration Of Eye Cosmetic Productsmentioning
confidence: 99%
See 4 more Smart Citations
“…The migration of externally applied eye cosmetics onto the ocular surface has been consistently reported 6,7,11,12,14. There have been numerous anecdotal accounts of tear film contamination with eye cosmetic products during routine slit lamp examination 6,12.…”
Section: Ocular Migration Of Eye Cosmetic Productsmentioning
confidence: 99%
“…There have been numerous anecdotal accounts of tear film contamination with eye cosmetic products during routine slit lamp examination 6,12. Prospective studies have confirmed that tear film contamination can result from passive and inadvertent migration of periocular cosmetic products across the eyelid margin, in addition to poor application techniques, direct accidental ocular instillation, and eye rubbing 6,11.…”
Section: Ocular Migration Of Eye Cosmetic Productsmentioning
confidence: 99%
See 3 more Smart Citations